Accented Cinema. The Stylistic Approach - Naficy, Hamid (Iluminace, 2008)
The translation of the chapter from Hamid Naficy's book focuses on the exile cinema of filmmakers mainly from Iran, or from the Third World in the USA, but provides a comprehensive conceptual and methodological apparatus for the whole issue. The author clearly and systematically presents his conception of ``style with an accent,'' including a table listing the basic stylistic elements.
Keywords: emigrants; exile film; film aesthetics; narration in film; film theory